Aggregate Imports and Expenditure Components in the Philippines: An Econometric Analysis - Frank W. Agbola (India Economic Review, 2009)
This paper estimates aggregate short-run and long-run import demand functions for the Philippines using data for the period 1960-2006. Results indicate that import demand and its determinants are cointegrated in the long run. The import demand with respect to expenditure components is inelastic in both the short run and long run. The error correction mechanism indicates that equilibrium is attained in nearly two years after a shock to expenditure components of the import demand function. Short-run determinants of import demand are exports and domestic investment, while the long-run determinants of import demand are exports, domestic investment and government expenditure